Complete genome annotation data of Mycobacteriophages Prann and LeoAvram: New members of the family Siphoviridae - Pragati Jamdagni; Kiran Nehra; J.S. Rana; Louise M. Temple (Data in Brief, 2023)
Two novel mycobacteriophages (Prann and LeoAvram) belonging to the family Siphoviridae were isolated from soil samples of Northern India. Genomic DNA of both the phages was extracted, and further sequenced using Illumina technology. Complete genome annotation of both the isolates was performed using DNA Master. Prann and LeoAvram had linear genomes of 68398bp and 47079bp, respectively, with G+C contents of 60-70%. A total of 99 and 75 ORFs were predicted in Prann and LeoAvram, respectively. Based on sequence similarity to known phage proteins, functions were assigned to 44 and 53 genes, respectively. These proteins could be classified into five major groups, viz., phage structural proteins, proteins for recombination, lytic enzymes, proteins involved in DNA / RNA metabolism, and in regulation. Mycobacterium smegmatis was used in this work as a safe surrogate for Mycobacterium tuberculosis, the causative agent for tuberculosis, a major infectious disease worldwide with developing antibiotic resistance. This is the first report of M. smegmatis phages from Northern India.